Trading off generations: Infinitely lived agent versus OLG - Maik T. Schneider; Christian Traeger; Ralph Winkler (Center for Economic Studies and ifo Institute (CESifo), 2012)
The prevailing literature discusses intergenerational trade-offs in climate change predominantly in terms of the Ramsey equation relying on the infinitely lived agent model. We discuss these trade-offs in a continuous time OLG framework and relate our results to the infinitely lived agent setting. We identify three shortcomings of the latter: First, underlying normative assumptions about social preferences cannot be deduced unambiguously. Second, the distribution among generations living at the same time cannot be captured. Third, the optimal solution may not be implementable in overlapping generations market economies.
Keywords: D63; H23; Q54; 330; climate change; discounting; infinitely lived agents; intergenerational equity; overlapping generations; time preference; Klimaveränderung; Generationenbeziehungen; Zeitpräferenz; Overlapping Generations; Theorie